2004
DOI: 10.1002/cne.20082
|View full text |Cite
|
Sign up to set email alerts
|

The 5‐HT2A receptor is widely distributed in the rat spinal cord and mainly localized at the plasma membrane of postsynaptic neurons

Abstract: Serotonin (5-HT) plays a major role at the spinal level by modulating most spinal functions through several receptor subtypes including the 5-HT2A receptor. To gain further insight into the cellular role of this receptor, we performed an immunocytochemical study of 5-HT2A receptors in the rat spinal cord, at light and electron microscope levels. The results showed that 5-HT2A receptors were widely distributed in the spinal cord at all segmental levels. Immunolabeling was particularly dense in lamina IX and in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
57
3

Year Published

2004
2004
2012
2012

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 97 publications
(69 citation statements)
references
References 69 publications
8
57
3
Order By: Relevance
“…The absence of extracellular plasma membrane staining for 5-HT5AR is in complete contrast with observations made for 5-HT2AR in the rat dorsal horn using an antibody also recognizing an N-terminal sequence of the receptor (Doly et al, 2004). In the latter case, we observed dense staining localized in the extracellular space and outlining a large surface of the plasma membrane.…”
Section: Discussioncontrasting
confidence: 84%
“…The absence of extracellular plasma membrane staining for 5-HT5AR is in complete contrast with observations made for 5-HT2AR in the rat dorsal horn using an antibody also recognizing an N-terminal sequence of the receptor (Doly et al, 2004). In the latter case, we observed dense staining localized in the extracellular space and outlining a large surface of the plasma membrane.…”
Section: Discussioncontrasting
confidence: 84%
“…Interestingly, both ␣ 1 and 5-HT 2 agonists inhibited the amplitude of polysynaptic reflexes recorded from both L2 and L5 neurograms. Other reports have showed inhibition of spinal reflexes by 5-HT 2 in neonatal rats (Yomono et al 1992), and high expression of 5-HT 2 receptors have been reported in lamina II of rats (Doly et al 2004). The inhibition of afferent transmission may be due to potentiation of glycine conductances in first-order dorsal horn neurons by activation of inhibitory interneurons (Li et al 2002).…”
Section: Monoaminergic Modulation Of Rhythmic Activitymentioning
confidence: 82%
“…This effect was very likely due to the restoration of endogenous inhibition, because slight changes in E Cl were shown to have an important impact on the strength of inhibition (5-7, 10). 5-HT 2A Rs are strongly expressed in the ventral horn (45) and are mainly localized in the plasma membrane of neurons, covering a large surface of cell bodies and dendrites (46). These receptors are dramatically up-regulated in the motoneuron somata and dendrites following SCI (47), an effect that starts as early as 1 d after transection (48).…”
Section: Discussionmentioning
confidence: 99%